Recursos Montessori para el aprendizaje de operaciones de suma y resta en segundo grado de la Escuela “Lauro Damerval Ayora”, Loja 2023 - Sánchez Cuenca, Valeria Alexandra (2023)
The implementation of Montessori resources in the teaching of addition and subtraction operations, is an effective strategy to improve the learning of mathematics in second grade children. This research paper called The use of Montessori resources for the learning of addition and subtraction operations in second grade students from the "Lauro Damerval Ayora" School, Loja 2023, has set as the general objective to analyse the incidence of Montessori resources in the learning of addition and subtraction operations of second grade children. This study was executed using a mixed approach, that is, of a quantitative and qualitative nature, along with a descriptive research type. It is a non-experimental research design; the methods used are scientific, inductive, deductive, analytical, synthetic and statistical; the techniques applied were a survey aimed at teachers, and an evaluation applied to students. The initial evaluation main result documented that the students were close to achieving the required learning, but after the application of the proposed plan, a high percentage of them managed to master the required learning; therefore, it is concluded that the preparation and implementation of this didactic proposal managed to create a positive impact on the learning process of addition and subtraction operations in the above-mentioned students, consequently, it is recommended that the Unidad Educative "Lauro Damerval Ayora" consider expanding the implementation of Montessori resources in other teaching areas. Key words: Montessori resources, teaching-learning, mathematics, Montessori pearls.